Molecular doped organic semiconductor crystals for optoelectronic device applications. Issue 43 (23rd September 2020) - Qin, Zhengsheng; Gao, Can; Wong, Wallace W. H.; Riede, Moritz K.; Wang, Tianyu; Dong, Huanli; Zhen, Yonggang; Hu, Wenping
Abstract : In this review, we give a timely summary of the current progress of molecular doped organic semiconductor single crystals in terms of material selection, crystal growth, resulting properties and device applications. Abstract : For semiconductors, doping is an efficient approach to tune their energy bandgaps, charge transport, and optical properties which could enable the improvement of the corresponding performances and open up the possibility of multifunction integration. Recently, significant advances have been achieved in molecular doped organic semiconductors, especially doped organic semiconductor single crystals (OSSCs) which have features of well-defined packing structures, long-range molecular orders, and low-density defects for fundamental studies and improved properties. In this review, we will give a summary of the exciting progress of molecular doped OSSCs from the aspects of selection criteria of molecular dopants, general growth methods, and resulting optoelectronic properties as well as their applications in optoelectronic devices. Finally, a brief conclusion is given with challenges and perspectives of molecular doped OSSCs and their related promising research directions in this field.